Plant-human entanglements in buildings: designing for care infrastructuring with office occupants and pot plants - Loh, Susan; Santo, Yasu; Foth, Marcus (Frontiers in Computer Science, 2023)
The current outsourcing of maintenance and the use of technological devices to automatically care for plants in buildings change the spatial experience between human office occupants and plants. This caretaker system distances people from plants, inclining us to regard them more as decorative objects. The relationship between humans and plants in a building is often unidirectional, with plants providing humans multiple benefits such as improved health and well-being, and increased worker productivity. In our human-plant interaction study, we developed a layer of care infrastructure within an office building that gives agency to people as a collective to interact with and take care of other non-human beings; that is, plants. In re-imagining mediated human-building interaction, we employed technology as an ambient mediator where people, plants and technology comprised the plant care system in a typical office building. Additionally, through qualitative interviews of study participants, we identified five themes: Technology, Object/Thing, Infrastructuring, Commoning, and Care. Our analysis of these themes informs a care infrastructuring approach where both humans and plants become interdependent office co-inhabitants. By entangling with technology, care, and others, we present an infrastructuring layer to mediate humanbuilding interactions with plants.